Cardiac autonomic control during platelet apheresis (Annals of Medical Research, 2022)
Aim: The aim of the current study was to assess the effects of platelet apheresis (PA) on cardiac autonomic control by the means of short-term heart-rate variability (HRV) technique.Materials and Methods: A total of 100 platelet donors (age: 29.0±0.9 years, body mass index: 25.8±0.7) were evaluated for heart rate (HR), HRV and blood pressure through a full cycle of PA. HR and HRV were assessed by 5-min continuous electrocardiographic recordings at four occasions, i.e., 5 min before (-5 min), and at 10th min (10 min), 45th min (45 min) and at post 5th min of PA. Time- and frequency-domain parameters of HRV were calculated using specific software. Low-frequency (LF)/high-frequency (HF) ratio was also determined. Blood pressure (BP) was also recorded 5 min before and 5 min after PA.Results: HR increased towards 45th min and declined towards the end of the PA (P
Keywords: Cardiac autonomic control; heart rate variability; platelet apheresis